Legal Protection of Indigenous Land Rights: A Study of Customary Law Integration in National Legal - Maswatu, Ismail; Santosa, Tomi Apra; Ghoni, Abdul; Dewi, Mira Nila Kusuma; Taqiyuddin Kadir; Hartawati, Andi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The protection of indigenous land rights is a crucial aspect in safeguarding the identity, culture, and economic sustainability of indigenous communities. This study examines the integration of customary law (hukum adat) into the national legal framework as a means to ensure legal certainty and justice for indigenous peoples. Using a normative juridical approach supported by statutory, conceptual, and case analysis, the research explores how national regulations accommodate the recognition, protection, and enforcement of customary land rights. The findings reveal that although the Constitution and several sectoral laws explicitly acknowledge the existence of customary law, their implementation is often hindered by overlapping regulations, weak institutional mechanisms, and the dominance of state-centered land policies. The study argues that effective integration requires harmonization between customary norms and national legislation, the establishment of participatory dispute resolution mechanisms, and the strengthening of institutional capacity to recognize and register indigenous territories. This research contributes to the discourse on legal pluralism by offering a framework for integrating customary law into national law without eroding its unique characteristics, thereby promoting both social justice and sustainable land management.